1996
DOI: 10.1097/00007632-199603010-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study of the Fibrous Capsule of the Human Lumbar Facet Joint

Abstract: Anatomical and histologic features of the lumbar facet joint capsule are different between its outer layer and inner layer. This complex of morphologic factors can affect the biomechanics and neurophysiology of the lumbar facet joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 8 publications
2
65
0
Order By: Relevance
“…Several studies have reported that the greatest loads experienced by the facet joints occur during extension. [1][2][3][4]10,12,13,17 Current treatment options for facet-induced lower back pain include arthrodesis and therapeutic injection. Both treatment options have had limited success with long-term LBP relief.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that the greatest loads experienced by the facet joints occur during extension. [1][2][3][4]10,12,13,17 Current treatment options for facet-induced lower back pain include arthrodesis and therapeutic injection. Both treatment options have had limited success with long-term LBP relief.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 The capsule surrounding the facet joint has been shown to be well innervated by afferent nociceptive fibers, which are activated by mechanical stresses. 1,2,4,6,7,11 Several in vitro studies and analytical models have confirmed that facet loading is increased during extension. [5][6][7][8][12][13][14][15] Shirazi-Adl and Drouin showed that the facets carry as much as 30% of the load in the presence of 2°to 5.6°of extension rotation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Anatomical studies of the facet capsule evaluating the macroscopic and microscopic matrix composition and orientation of those components have shown that the facet capsule is composed of an outer layer of primarily collagen fibers orientated across the facet joint, while in its inner layer there are more randomly orientated elastic fibers. 111,112 The thickness of the outer layer of the capsule, and the length of the collagen fibers within it, vary with the anatomic location of the capsule, as does the proportion of elastic fibers within the collagen matrix. 111,112 Because the microstructure of the capsular ligament dictates the biomechanical function and potential for injury, any variation in capsular microstructure likely corresponds to the functional ability of the capsule to guide and limit motions of the facet joint.…”
Section: Kinematics and Facet Tissue Injury During Whiplashmentioning
confidence: 99%
“…111,112 The thickness of the outer layer of the capsule, and the length of the collagen fibers within it, vary with the anatomic location of the capsule, as does the proportion of elastic fibers within the collagen matrix. 111,112 Because the microstructure of the capsular ligament dictates the biomechanical function and potential for injury, any variation in capsular microstructure likely corresponds to the functional ability of the capsule to guide and limit motions of the facet joint. The greater proportion of elastic fibers in the posteroinferior aspect corresponds to the large strains that are sustained in that region during extension and the potential for recovery to the neutral position with minimal risk of impingement.…”
Section: Kinematics and Facet Tissue Injury During Whiplashmentioning
confidence: 99%